2014
DOI: 10.1016/j.jtcvs.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Toward individualized management of the ascending aorta in bicuspid aortic valve surgery: The role of valve phenotype in 1362 patients

Abstract: The individualized, multifactorial management of AA in patients with BAV during aortic valve surgery leads to excellent results. The threshold AA diameter for intervention (AoP or AAR) varied from 34 to 51 mm (mean, 43.9). BAV type 2/unicuspid and BAV type 1 LR with regurgitation emerged as determinants for more liberal AAR in our practice. Longer term follow-up is necessary to confirm our conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…Pathology studies also found worse elastic fiber loss in aortic wall tissue of BAV-AI patients, 31, 32 which is in accordance with clinical observations that BAV-AI patients, especially those with predominantly sinus dilatation (so-called “root phenotype”), suffered from faster ascending aorta dilatation and higher risk for adverse aortic events even after aortic valve replacement. 1315, 3335 In advent of above evidences, an aggressive policy of preventive aortic intervention might be appreciated in BAV-AI patients who exhibit a uniform WSS elevation around the lumen of the ascending aorta, and who are also known to present at a younger age and with the “root phenotype”. Meanwhile, BAV-AS patients who exhibit exaggerated flow eccentricity and elevation of regional WSS could benefit from less aggressive treatment strategies including reduction aortoplasty guided by WSS mapping.…”
Section: Discussionmentioning
confidence: 99%
“…Pathology studies also found worse elastic fiber loss in aortic wall tissue of BAV-AI patients, 31, 32 which is in accordance with clinical observations that BAV-AI patients, especially those with predominantly sinus dilatation (so-called “root phenotype”), suffered from faster ascending aorta dilatation and higher risk for adverse aortic events even after aortic valve replacement. 1315, 3335 In advent of above evidences, an aggressive policy of preventive aortic intervention might be appreciated in BAV-AI patients who exhibit a uniform WSS elevation around the lumen of the ascending aorta, and who are also known to present at a younger age and with the “root phenotype”. Meanwhile, BAV-AS patients who exhibit exaggerated flow eccentricity and elevation of regional WSS could benefit from less aggressive treatment strategies including reduction aortoplasty guided by WSS mapping.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of BAV morphotypes is consistent with previous work from our laboratory 8 and others. 7,9 …”
Section: Methodsmentioning
confidence: 99%
“…The decision for AAR concomitant to the valve surgery was based on a multifactorial policy presented in detail elsewhere. 9 In brief, the following factors were included: diameter of the AA around 45 mm, BSA, sex, age-more progressive decision in young age-fragility of the wall of the AA, progressive increase of AA diameter (0.5 cm per year), family history of aortic disease, BAV type 1 with insufficiency and BAV type 2/unicuspid, phenotype III and IV of AA according to Fazel and colleagues. 16 Age, especially young age, was of special concern for decision making, because age is the most powerful determinant of growth and young age shows faster growth of AA diameters.…”
Section: Surgerymentioning
confidence: 99%